Efficient DNS based Load Balancing for Bursty Web Application Traffic - Chin, Mei Lu; Chong, Eng Tan; Mohamad Imran, Bin Bandan (IJMCIS, 2012)
This research proposes a new efficient load balancing algorithm which applies to the local Domain Name Service (DNS) server for web based applications and services to ease the sudden increase in demand for the services. Owing to the existing load balancing algorithms still experience server’s resource congestion and slow connection to the system resulted by sudden bursty demand of services especially during special events. This is mainly due to the unbalanced distribution of workload and the insufficient of physical computing resources in service provision. To overcome this problem, most web based application service providers will have to constantly improve the capacity of their physical computing resources by either adding new server nodes to the existing server farm or renting cloud computing resources from cloud computing service provider to meet the sudden demands of the end users during the peak period. However, it is not economical to maneuver and reconfigure huge amount of permanent computing resources just to satisfy the instantaneous and short period of service demand. As a result, the need to have a more efficient load balancing algorithm which can adaptively utilize the resources available in the farm of computing resources will be of advantageous. The new algorithm will be able to directly decrease the operation cost and web services will no longer be interrupted by sudden high demand of traffic request. The proposed algorithm is evaluated via computer simulation and modeling where its performance is verified against the few selected algorithms of the same nature. Enhancement on the DNS system for load balancing is beneficial to most organizations such as government agencies and service providers running their own local DNS service, which allow the proposed algorithm to be easily implemented. Moreover, DNS setup is standard across the IP networks hence the adoption can be easy achieved with minimal changes without altering the architecture of the services provided especially in coding as well as physical set up of the server farm itself.